Assessment of the Effectiveness of Fascial Manipulation in Patients with Degenerative Disc Disease of the Lumbosacral Spine - Anna Mikołajczyk-Kocięcka; Marek Kocięcki; Lech Cyryłowski; Aleksandra Szylińska; Paweł Rynio; Magdalena Gębska; Ewelina Szuba; Jarosław Kaźmierczak (Life)
Background: The aim of this study was to evaluate the effectiveness of Fascial Manipulation in patients with disc herniations of the lumbar spine confirmed by magnetic resonance imaging. Material and Methods: This study included 69 patients with intervertebral disc damage of the lumbar spine, as confirmed by magnetic resonance imaging. Patients were divided into two groups: a study group and a control group. The control group (C) was treated conservatively with treatments such as interference currents, diadynamic currents, tens currents, galvanization, Sollux lamps, local cryotherapy, magnetic fields, therapeutic massages of the spine, and mobility exercises. The study group (S) was subjected to therapy using Fascial Manipulation, which included two treatments—the first on the day the patient reported for the study and the second a week later. Patients for this study were selected at random. Results: This study presents a statistically significant difference between the treatment effects, as assessed by the degree of pain (p < 0.001) and mobility limitation (p < 0.001), as well as the presence of stretch symptoms (p < 0.001): all three parameters improved significantly more in the study group compared to the control group. Conclusion: Fascial Manipulation is an effective method for treating pain in patients with disc herniations of the lumbar spine; in addition to reducing pain, it improves the range of motion and the results of SLR and PKB tests. In lumbar spine pain in disc herniations, treatment using Fascial Manipulation is definitely more effective than treatment according to the traditional physiotherapy regimen.